From Black to Contemporary Cariology: Learning to look at the same lesions with a different perspective - Gudiño DDS, MPH, Sylvia; Lanata DDS, PhD, Eduardo (Odovtos - International Journal of Dental Sciences, 2015)
Since its birth as a profession and in the XIXth and XXth centuries, Dental Sciences generated overwhelming amount of new knowledge in Cariology, in such dispair areas as basic sciences, tissue engineering and regeneration, microbiology, endogenous and exogenous nutritional factors, social sciences, etc., as well as in prevention, diagnosis, classification, activity, control, monitoring, treatment and rehabilitation of carious lesions. However, according to the Centers for Disease Control, USA (1), the problem still remains: in childhood tooth decay is the most common chronic disease, and in teenagers from 14 to 17 years old is 4 times more common than asthma. Many adults suffer the disease without treatment, determining the progression of lesions, fact that affects its quality of life. This new perspective article presents relevant and recent information on the Cariology of the XXI Century, that could help reversing the state described.